Desenvolvimento de phantom antropomórfico cerebral para simulação de atividade ICTAL e imterictal utilizando a metodologia pet com flúor-18 - Silbermann, Karina Nique Franz (2018)
The equipment and processes used in nuclear medicine must be included in a quality control program that includes a series of tests and calibrations following the frequency established by current standards, which are based on international institutions protocols. The capability of anthropomorphic simulators mimic realistic situations are widely appointed to gauge essential data that guarantee the quality in medical generating processes. The purpose of this study was developing a cerebral anthropomorphic phantom for image simulation of ictal activity in nuclear medicine with 18F, PET-CT. It was made in an industrial printer with SLS (Selective Laser Sintering) technology, 4mm thick, using nylon 12. The model was segmented from a magnetic resonance study of a 40-year-old female adult. Two 40 nm thickness metal (Ag) electrodes were inserted in the right frontal lobe region to simulate ictal activity. For the images acquisition, the phantom was filled with distillated water and the 18F radioisotope. The images were acquired in PET-CT equipment with specific protocol for tomographic and dynamic cerebral studies. Images from the simulator without the insertion of the electrodes were acquired as pattern (basal), also were acquired images from the simulator with the electrodes and without electric field application, and the simulator with electric field application. The images were compared through SUV maximum values and uptake index. The non-parametric Wilcoxon-Mann-Whitney test was used as statistic approach, considering the three image conditions as independent groups. There was significant difference amongst the groups, being p < 0,001 when compared the average SUV maximum values by slices in the situations: basal x with electric field, and basal x without electric field, p = 0,129 when compared situations with electric field x without electric field, suggesting that this difference is not significant. All the groups presented significant differences for the uptake indexes obtained, being p < 0,001 in the situations basal x with electric field and basal x without electric field. The TAC (time-activity-curve) curves were obtained in A PET-CT dynamic protocol to demonstrate the 18F uptake in time, in the conditions with electric field and without electric field. The images were subtracted through SISCOM, using the basal condition as reference. The values found for p (SUV and uptake index) are compatible. The SISCOM histograms demonstrate differences for the three image comparisons. Although there are gradual raise of 18F uptake in time obtained in TAC evaluation for both with and without electric field conditions, the highest uptake visualized was when the electric field is applied. The anthropomorphic phantom developed is capable of simulating compatible zones with ictal activity, however the material used as resin in the electrodes must be modified so that the product may be commercialized in the future.